Effort to Get Reading Interest Through Parenting - Marti, Marti; Labibah, Labibah (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2024)
The influence of the family in developing an interest in reading is very large and very important. Families have the task of building a good reading culture, a culture that can condition families to be involved in good reading activities. Because reading can change each individual's perspective and direct their views outward. Through parental involvement, which is the main priority in developing interest in reading. Parental involvement is basically needed at all times for children at an early age, where at this age children begin to develop knowledge, attitudes, emotional morals and scharacter formation. Therefore, this research takes the title "Parenting as an Effort to Develop Interest in Reading". The aim of this research is to determine the influence of parents on children's interest in reading. This research method is qualitative using a descriptive approach. Namely collecting several literature in the form of articles and books that are related to this research. Many studies discuss increasing interest in reading, but none has touched on increasing interest in reading through parenting. Thus, this research will discuss efforts to increase children's interest in reading through parenting. The results obtained from this research are that parents have a very important influence on children's interest in reading because the family environment is a place to raise, educate and care for children. The family is the most important and first social group. Children will have their first interactions at the beginning of their life with the people closest to them. With several efforts made, including often reading books to children before bed, providing a reading corner at home, going to book bazaars for recreation, giving gifts of books to children, become the parents of your dreams.